Entrepreneurial Success through Microfinance Services among Women Entrepreneurs in Sri Lanka: A Pilot Study and Overview of the Findings - Bernard, D. T. Kingsley; Kevin, Low Lock Teng; Khin, Aye Aye (International Journal of Economics and Financial Issues, 2016)
Determining microfinance services which facilitate entrepreneurial success among women entrepreneurs who use such services remains a major issue in the microfinance sector. To address this gap, this study was designed to tap into microfinance services constructs as well as entrepreneurial success of women entrepreneurs within the conceptual model. The relevant questionnaire was piloted among 40 women through microfinance services in Sri Lanka. Based on theories, the measures which comprise microcredit, micro-saving, micro-insurance, business-support, skills development and dependent variable of the entrepreneurial success among women through micro finance were derived from the literature and expert opinion. These constructs were subject to reliability and validity tests to decide on the measures and items to be retained to represent microfinance services and entrepreneurial success in microfinance sector in Sri Lanka. The findings of the study will provide a good starting point to identify the suitable measurements. Further the study will pave way for a comprehensive study which can develop a diamond specification model for the financial sector in Sri Lanka. Keywords: Entrepreneurial success, Microfinance Services, Women in Sri Lanka. JEL Classifications: G21, L26